2022
DOI: 10.3390/nano12071126
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Genotoxic Effects of Gold Nanoparticles Functionalized with Seven Different Ligands in Cultured Human Hepatocellular Carcinoma Cells

Abstract: Gold nanoparticles (GNPs) have shown great potential in diagnostic and therapeutic applications in diseases, such as cancer. Despite GNP versatility, there is conflicting data regarding the toxicity of their overall functionalization chemistry for improved biocompatibility. This study aimed to determine the possible genotoxic effects of functionalized GNPs in Human hepatocellular carcinoma (HepG2) cells. GNPs were synthesized and biofunctionalized with seven common molecules used for biomedical applications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Besides controlling the particle size and shell thickness, previous reports highlight that GSH capping also plays a role in cellular internalization and biocompatibility. For instance, GSH-stabilized AuNPs displayed fivefold higher cellular internalization than Tri-Na-stabilized AuNPs . Another recent report highlighted GSH-stabilized AuNPs inducing reversible DNA damage compared to Tri-Na-stabilized AuNPs, which led to irreversible DNA damage in HeLa cells .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides controlling the particle size and shell thickness, previous reports highlight that GSH capping also plays a role in cellular internalization and biocompatibility. For instance, GSH-stabilized AuNPs displayed fivefold higher cellular internalization than Tri-Na-stabilized AuNPs . Another recent report highlighted GSH-stabilized AuNPs inducing reversible DNA damage compared to Tri-Na-stabilized AuNPs, which led to irreversible DNA damage in HeLa cells .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, GSH-stabilized AuNPs displayed fivefold higher cellular internalization than Tri-Na-stabilized AuNPs . Another recent report highlighted GSH-stabilized AuNPs inducing reversible DNA damage compared to Tri-Na-stabilized AuNPs, which led to irreversible DNA damage in HeLa cells . Another independent report highlighted citrate-stabilized AuNPs inducing liver inflammation compared to HEPES-stabilized AuNPs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[56] Previous studies have shown that metal-based nanoparticles have a nonspecific bacterial mechanism of action (they do not bind to specific receptors in bacterial cells), which not only makes it difficult for bacteria to develop resistance, but also broadens the range of antibacterial activity. [57] However, metal nanoparticle-based AMPs as novel antimicrobial agents for [53] Copyright 2016, American Chemical Society. B) Formation of AgNPs on PA nanofibers.…”
Section: Amp Metal Nanoparticle Self-assembly Therapymentioning
confidence: 99%
“…[ 56 ] Previous studies have shown that metal‐based nanoparticles have a nonspecific bacterial mechanism of action (they do not bind to specific receptors in bacterial cells), which not only makes it difficult for bacteria to develop resistance, but also broadens the range of antibacterial activity. [ 57 ] However, metal nanoparticle‐based AMPs as novel antimicrobial agents for treating bacterial infections, have not shown excellent therapeutic effects in mouse models. Compared with the rest of the previously described self‐assembled peptides, there is still a gap in the reduction of organ bacterial load and inflammatory damage.…”
Section: Abdominal Infectionmentioning
confidence: 99%